IMPLEMENTASI INOVASI PELAYANAN LANGSUNG DARI PINTU KE PINTU (PALANG PINTU) BAGI MASYARAKAT DISABILITAS DAN LANSIA DI KOTA PADANG PANJANG - Reffisca Hidayat; Syamsir (ADMIN: Jurnal Administrasi Negara, 2023)
This study intends to find out the implementation of direct service innovations (PALANG PINTU) for people with disabilities and the elderly in Padang Panjang City. This research was conducted using a qualitative approach with descriptive methods, in determining the informants researchers used purposive sampling methods and techniques. For data collection techniques carried out by interviews, observation, and documentation. In testing the validity of the data, researchers used the source triangulation technique. As for data analysis techniques using data reduction, data presentation and drawing conclusions. The results showed that there were 2 influencing factors, namely supporting factors such as human resources and commitment from the Padang Panjang City Discipline. Meanwhile, the inhibiting factors are the lack of community participation and the limited means of implementing activities and the budget.